KAJIAN HUKUM PROGRESIF TERHADAP PASAL 2 UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Safira, Martha Eri (IAIN Ponorogo, 2012)
Martha Eri SafiraAbstract: A marriage, refers to legal law of marriage article 2, is legitimate if the doers marry under their religious law. A legal marriage refers both to doersâ religious procedures and to society perspective. Nevertheless, the most important thing is that government trough its officers should legalize the marriage for legal reason. An illegal marriage and divorce will drive to problematic level. It is probably legal for society but illegal to marriage officers as âpencatat nikahâ who base their legality to legal law of marriage. The former, consequently, takes ânegative domino effectâ not only for a wife but also for her kids legally and socially. This short paper is to elaborate legal law of marriage by using both progressive law, shari>âah law and law educational system. Do progressive law and the others afford and give solution to protect women and their kids legally and socially?Keywords: Perkawinan di bawah tangan, hukum progresif, hukum perkawinan, dan penegakkan hukum